2021
DOI: 10.1186/s12883-021-02353-y
|View full text |Cite
|
Sign up to set email alerts
|

Stroke risk factors, subtypes and outcome in elderly Thai patients

Abstract: Background Nowadays, the number of elderly has steadily increased annually. Elderly patients with ischemic stroke often have worse outcomes than younger patients. However, there has not been a study of ischemic stroke in the elderly in Thailand. A better knowledge of the risk factors, subtypes, and outcomes of strokes in the elderly may have significant practical implications for the aged society in the future. The objective of the study was to assess the risk factor, stroke sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
(19 reference statements)
0
10
0
1
Order By: Relevance
“…Predicting long-term mortality can help guide decisions about ongoing medical management, such as the use of secondary prevention measures, and can also inform discussions about end-of-life care. Several features have been identified that are strongly associated with death in patients with ischemic stroke, namely, age (4)(5)(6), underlying dementia (7), underlying cancer (5,6), white blood cells (WBC) (6), anion gap (AG) (8), mechanical ventilation (MV) (9), and osmotic therapy (10).…”
Section: Introductionmentioning
confidence: 99%
“…Predicting long-term mortality can help guide decisions about ongoing medical management, such as the use of secondary prevention measures, and can also inform discussions about end-of-life care. Several features have been identified that are strongly associated with death in patients with ischemic stroke, namely, age (4)(5)(6), underlying dementia (7), underlying cancer (5,6), white blood cells (WBC) (6), anion gap (AG) (8), mechanical ventilation (MV) (9), and osmotic therapy (10).…”
Section: Introductionmentioning
confidence: 99%
“…More than 85% of all strokes occur in populations over 65 years old, while 72% occur in those ≥75 years [4]. Patients <65 years are reported to present with less severe stroke and better outcomes when compared to ≥75 years of age group [5,6]. This finding suggests that specific age-related risk factors may differentially contribute to stroke severity in patients 65 and 74 years old when compared with those ≥75 years.…”
Section: Introductionmentioning
confidence: 98%
“…However, how HF and other risk factors contribute to stroke severity in older patients is not fully understood. This is because most studies regarding stroke in the elderly population did not differentiate between risk factors associated with 65-74 years old patients where the stroke is reported to be less severe compared with ≥75 where stroke severity is higher [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, accounting for around 14% of all strokes in the UK, and linked to a significantly high risk of developing ischaemic stroke (Workman et al ., 2008; Samuthpongtorn et al ., 2021). The prevalence of AF in the general population is 2%, although AF is age-dependent and this figure rises to 3.7-4.2% in ages 60-70 and 10-17% in the over 80s (Zoni-Berisso et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%